Applicability of ancestral genotyping in pharmacogenomic research with hormonal contraception - Aaron Lazorwitz; Christina L. Aquilante; Jonathan A. Shortt; Jeanelle Sheeder; Stephanie Teal; Christopher R. Gignoux (Wiley, 2021)
Abstract To compare etonogestrel pharmacokinetic and pharmacodynamic outcomes by both self‐reported race/ethnicity and genetically determined ancestry among contraceptive implant users. We conducted a secondary analysis of our parent pharmacogenomic study of 350 implant users. We genotyped these reproductive‐aged (18-45 years) women for 88 ancestry‐informative single nucleotide polymorphisms. We then assigned each participant a proportion value for African (AFR), European (EUR), and Indigenous American (AMR) ancestry based on reference population data. We correlated genetic ancestry with self‐reported race/ethnicity and utilized genetic ancestry proportion values as variables for previously performed association analyses with serum etonogestrel concentrations and progestin‐related side effects (e.g., bothersome bleeding and subjective weight gain). We successfully estimated genetically determined ancestry for 332 participants. EUR, AFR, and AMR ancestry were each highly correlated with self‐reported White/non‐Hispanic race (r = 0.64, p = 4.14 × 10−40), Black/African American race (r = 0.88, p = 1.36 × 10−107), and Hispanic/Latina ethnicity (r = 0.68, p = 4.03 × 10−47), respectively. Neither genetically determined ancestry nor self‐reported race/ethnicity were significantly associated with serum etonogestrel concentrations. AFR ancestry and self‐reported Black race had similar associations with reporting monthly periods (odds ratio [OR] 2.18, p = 0.09 vs. OR 2.22, p = 0.02) and having received treatment for bothersome bleeding (OR 5.19, p = 0.005 vs. OR 4.73, p = 2.0 × 10−4). In multivariable logistic regression for subjective weight gain, AMR ancestry dropped out of the model in preference for self‐reported Hispanic/Latina ethnicity. We found no new associations between genetically determined ancestry and contraceptive implant pharmacodynamics/pharmacokinetics. Self‐reported race/ethnicity were strong surrogates for genetically determined ancestry among this population of contraceptive implant users. Our data suggest that self‐reported race/ethnicity, capturing societal and cultural aspects, remain important to the investigation of progestin‐related side effects.